Church Music Education for Sunday School Children: Strategies for Developing Church Music Ministers at the Indonesian Baptist Church of Solo - Ferbian Widi Pradana; Irfanda Rizki Harmono Sejati (CV. Edujavare Publishing, 2026)
Since 2021, in the post–COVID-19 pandemic period, the Gereja Baptis Indonesia (GBI) Solo has faced the need for regeneration of church music ministers due to the declining involvement of adult congregational musicians in worship services. This phenomenon has encouraged the church to develop church music education for Sunday School children as an effort to nurture music ministry from an early age. This study aims to describe the strategies of church music training for Sunday School children at GBI Solo and to analyze their role in developing children’s musical skills and spiritual character as prospective church music ministers. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, while data analysis was conducted interactively, with data validity ensured through source, technique, and time triangulation. The findings indicate that church music training is implemented through a learning by doing approach that is gradual, adaptive, and integrated into church worship activities. This strategy is effective in developing children’s musical skills while instilling faith-based values and character, including discipline, responsibility, cooperation, and humility, supported by synergistic collaboration among instructors, the church, and parents. The implications of this study suggest that experience-based and collaborative church music education can serve as a sustainable strategy for preparing future generations of church music ministers. The conclusion confirms that contextual and collaborative church music training strategies are able to effectively address the need for the regeneration of church music ministers.